Embedded Photographic Tomography Using Raspberry Pi - Rujipas Janthraprasert; Chuchart Pintavirooj (My University, 2022)
A computerized tomography scan (CT scan) is a device that uses X-ray machines and computers that will compute the data gathered from patients to create cross-sectional images. A CT scan can be used to view the inside without cutting the body open, such as blood vessels and different organs. However, most CT scan is mainly located at the hospital because it is very expensive and must be supervised at all times. So, it is hard for students to learn and understand the mechanic behind the actual CT scan. In this paper, we will build a simulated CT that can be used for educational purposes by creating an embedded photographic tomography using raspberry pi. The proposed system is capable of successfully creating a 3D model of the test object.
Keywords: Augmented Reality Applications; Medical Image Segmentation Techniques; Anatomy and Medical Technology